Combined Metabarcoding and Co-occurrence Network Analysis to Profile the Bacterial, Fungal and Fusarium Communities and Their Interactions in Maize Stalks - Cobo-Díaz, José Francisco; Baroncelli, Riccardo; Le Floch, Gaétan; Picot, Adeline (Frontiers in Microbiology, 2019)
Fusarium Head Blight (FHB) is one of the most devastating diseases of cereals worldwide, threatening both crop production by affecting cereal grain development, and human and animal health by contaminating grains with mycotoxins. Despite that maize residues constitute the primary source of inoculum for Fusarium pathogenic species, the structure and diversity of Fusarium spp. and microbial communities in maize residues have received much less attention than in grains. In this study, a metabarcoding approach was used to study the bacterial, fungal and Fusarium communities encountered in maize stalks collected from 8 fields in Brittany, France, after maize harvest during fall 2015. Some predominant genera found in maize residues were cereal or maize pathogens, such as the fungal Fusarium, Acremonium and Phoma genera, and the bacterial Pseudomonas and Erwinia genera. Furthermore, a high predominance of genera with previously reported biocontrol activity was found, including the bacterial Sphingomonas, Pedobacter, Flavobacterium, Pseudomonas and Janthinobacterium genera; and the fungal Epicoccum, Articulospora, Exophiala and Sarocladium genera. Among Fusarium spp., F. graminearum and F. avenaceum were dominant. We also found that the maize cultivar and previous crop could influence the structure of microbial communities. Using SparCC co-occurrence network analysis, significant negative correlations were obtained between Fusarium spp. responsible for FHB (including F. graminearum and F. avenaceum) and bacterial OTUs classified as Sphingomonas and fungal OTUs classified as Sarocladium and Epicoccum. Considering that isolates belonging to these taxa have already been associated with antagonist effect against different Fusarium spp. and/or other pathogenic microorganisms and due to their predominance and negative associations with Fusarium spp., they may be good candidates as biocontrol agents. Combining the use of Fusarium-specific primers with universal primers for bacteria and fungi allowed us to study the microbial communities, but also to track correlations between Fusarium spp. and other bacterial and fungal genera, using co-occurrence network analysis. Such approach could be a useful tool as part of a screening strategy for novel antagonist candidates against toxigenic Fusarium spp., allowing the selection of taxa of interest.